Day 2 Tue, November 13, 2018 2018
DOI: 10.2118/193190-ms
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Advanced Anlytics to Forecast Operational Upsets in Upstream Production System

Abstract: This paper highlights the development and results of an innovative tool for prediction of process upsets and hazard events associated with production operations of an oil and gas field. Summarily, this software can give recommendations on actions to mitigate or avoid operational issues, maximizing the asset value, while maintaining the highest safety and environmental quality. This in-house developed tool is based on big data analytics techniques such as machine and deep learning algorithms. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…As we have pointed out in our work, to maximize the effectivenss of the method, a business-oriented evaluation is required. In [5] the authors make similar considerations and propose an evaluation procedure for Machine Learning models trained to predict peaks in the SO2 emissions of an oil and gas treatment plant.…”
Section: Discussionmentioning
confidence: 99%
“…As we have pointed out in our work, to maximize the effectivenss of the method, a business-oriented evaluation is required. In [5] the authors make similar considerations and propose an evaluation procedure for Machine Learning models trained to predict peaks in the SO2 emissions of an oil and gas treatment plant.…”
Section: Discussionmentioning
confidence: 99%
“…The bootstrapping algo-rithm has been used for replication of sample data and in this work the authors utilized approximately 1,000 replicate wells' data. Cadei et al developed a model that can forecast the H2S trespassing events and provide a rapid and broad solution by analyzing the main cause to early troubleshoot the fault [17]. They also discussed the effectiveness of various ML models as binary classifiers such as logistic regression, decision tree, and neural networks for forecasting the H2S trespassing events and they found that neural networks achieve high accuracy where logistic regression and decision tree improve the transparency of the forecasting.…”
Section: ) Production Engineeringmentioning
confidence: 99%
“…Mineral extraction [130] Reservoirs modeling [42], management [104], evaluation [35], Upset and hazard prediction [17], [97], Casing damage prediction [78] Metal loss detection [82] Plants' health and safety [62] Business intelligence [12] techniques [64]. The architecture and process scheduling techniques of the manufacturing industry in the cloud service platform have been investigated in the context of big data analytics in the paper [51].…”
Section: Mine Construction Coal Mine Construction [129] Mineral Data ...mentioning
confidence: 99%
See 1 more Smart Citation
“…They analysed the collected data using eXtreme Gradient Boosting (XGBoost) and Multi-Layer Perceptron (MLP) neural networks to identify the potential operational gains. A range of studies analysed realtime data, historical data, maintenance reports, and operator data to improve O&G occupational safety and identify the underlying hidden trends [128]- [131].…”
Section: Decision Support Through Big Data Analyticsmentioning
confidence: 99%